Correction to: DNA copy number evolution in Drosophila cell lines. - Lee, H.; McManus, C.J.; Cho, D.Y.; Eaton, M.; Renda, F.; Somma, M.P.; Cherbas, L.; May, G.; Powell, S.; Zhang, D.; Zhan, L.; Resch, A.; et al. (Genome Biology, 2019)
Following publication of the original article [1], the authors reported the following errors.